Hyaluronic Acid After Subcutaneous Injection—An Objective Assessment. Issue 1 (January 2019) - Santer, Verena; Molliard, Samuel Gavard; Micheels, Patrick; Río-Sancho, Sergio del; Quinodoz, Pierre; Kalia, Yogeshvar N.; Salomon, Denis
Abstract : BACKGROUND: Hyaluronic acid (HA) fillers are the preferred injectable products for aesthetic correction of skin depressions and restoration of facial volume. OBJECTIVE: To investigate the subcutaneous distribution of 3, biophysically distinct, CE-marked and FDA-approved HA fillers. MATERIALS AND METHODS: BELB, JUVV, and RESL were injected ex vivo in porcine and human skin. Immediately after injection, the skin samples were snap-frozen, cross-sectioned, and visualized using stereomicroscopy and full-field optical coherence tomography. Images were compared with histological sections after hematoxylin and eosin staining. RESULTS: Hyaluronic acid fillers were distributed as homogeneous bolus in the ex vivo skin. The injection bulks were found to preserve the fibrous trabecular network, shift the fat lobules, and displace the adjacent adipocyte layers independently of the formulation injected. CONCLUSION: For the first time, the subcutaneous injection of 3 HA fillers with markedly different biophysical properties was systematically investigated by complementary visualization techniques. Despite their different properties, no difference in distribution was found after subcutaneous injection. The global preservation of the hypodermis structure observed was consistent with the good tolerability seen in clinical practice after implantation of the HA fillers in the subcutaneous skin layer.